Dampak Sosial Perlindungan Hukum Hak Cipta dan Merek di Kepulauan Riau - Devega, Widya; Muhammad, Adji Suradji; Setiawan, Ramadhani (Jurnal Ilmu Administrasi Negara (JUAN), 2019)
Intellectual Property Rights is one of strategic roles in advancing general welfare of the State. With Indonesia's background as one of the countries with largest IPR piracy cases in the world, it is hoped that with protection of law it can improve the image of Indonesia in the eyes of the world. The purpose of this study was to find out Social Impact of Copyright and Brand Legal Protection in the Riau Archipelago. The research method is qualitative with a descriptive approach. Informants in this study were an analysis of legal considerations for Intellectual Property Rights, creators, communities/consumers and public who did not register their work. From results of this study, it can be concluded that social impacts that occur will provide legal certainty for rights holders, develop creativity, feel anxious about the existence of piracy of works that have not been registered, and narrow space for the movement of Intellectual Property Rights violators, thus the products original will be circulating. Suggestion in this study is Ministry of Law and Human Rights of the Riau Archipelago Regional Office, which should evenly disseminate information to disseminate information on Intellectual Property Rights. Thus, public knows information such as costs, procedures, sanctions and the urgency of registering Intellectual Property Rights.